2012
DOI: 10.3109/10641955.2012.697953
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lymphangiogenic Factors in Preeclampsia

Abstract: Background Preeclampsia, a human pregnancy specific disorder is characterized by an anti-angiogenic state due to high levels of circulating soluble vascular endothelial growth factor 1 (sVEGFR-1). However, the role of lymphangiogenesis in preeclampsia has not been investigated. Recently, impaired VEGF-C (factor that regulates lymphangiogenesis) signalling has been implicated in the pathogenesis of interstitial edema and salt-sensitive hypertension. Therefore, we hypothesized that circulating VEGF-C and its cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…A study found that PE is characterized by decreased soluble VEGFR3, slightly decreased soluble VEGFR2, and increased VEGFC in the plasma; the level of soluble VEGFR-3 in PE plasma is consistent with the expression of VEGFR3 in the decidua in the present study [40]. However, these works concluded that decreased soluble VEGFR3 (sVEGFR3), slightly decreased sVEGFR2, increased VEGF-C, and dramatically low ratio of sVEGFR-2 þ sVEGFR-3/VEGF-C in the plasma show a circulating pro-lymphangiogenic state during PE; this condition may be a compensatory response to edema and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…A study found that PE is characterized by decreased soluble VEGFR3, slightly decreased soluble VEGFR2, and increased VEGFC in the plasma; the level of soluble VEGFR-3 in PE plasma is consistent with the expression of VEGFR3 in the decidua in the present study [40]. However, these works concluded that decreased soluble VEGFR3 (sVEGFR3), slightly decreased sVEGFR2, increased VEGF-C, and dramatically low ratio of sVEGFR-2 þ sVEGFR-3/VEGF-C in the plasma show a circulating pro-lymphangiogenic state during PE; this condition may be a compensatory response to edema and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…36,37 Among them, VEGF-C and VEGF-D are known to induce lymphangiogenesis through VEGF receptor (VEGFR)-2,3 signaling. 39 Recent studies reported that plasma levels of VEGFR-2, a crucial regulator of lymphangiogenesis, were decreased in preeclamptic women. 39 Recent studies reported that plasma levels of VEGFR-2, a crucial regulator of lymphangiogenesis, were decreased in preeclamptic women.…”
Section: Discussionmentioning
confidence: 99%
“…2830°C. [3] Hereby SiC decomposes into carbon and a silicon rich solution of up to 13 at % of carbon. In crystal growth technology SiC boules are mainly grown from the vapor by the so called physical vapor transport (PVT) method ( Figure 2).…”
Section: Silicon Carbidementioning
confidence: 99%